EFFECT OF STOPPING FERMENTATION OF Leuconostoc mesenteroides ATCC 10830 (8-512F) AT DIFFERENT GROWTH STAGES ON DEXTRAN FORMATION AND MEDIUM VISCOSITY - Triantarti Triantarti; J. P. Dufour (Jurnal Kimia Terapan Indonesia, 2000)
At the cut end of deteriorated sugar cane stalks, Leuconostocmesenteroides grows, secreting dextransucrase and formingdextran. When biocide is sprayed, bacteria will be killed butdextransucrase might still be active and forming dextran.In this experiment, it was found that when fermentation wasstopped (L. mesenteroi des were killed) this enzyme(dextransucrase) was still able to form high concentration ofdextran. The amount of dextran formed depended on the time offermentation. It also depended on the p H and temperature duringthe incubation which affect the activity and the stability ofdextransucrase. The higher the incubation temperature (20-30°C),the more sensitive dextransucrase activity to the pH changes (PH4.6 - 5.4). The highest dextransucrase stability during a 20 hincubation was found at pH 5,4. The highest activity was foundat 30°C for pH 5.4 while at 25°C the activity was only slightly10IVer than 30°C.Key words: dextran formation, medium viscosity,dextransucrase.